A situação escolar na perspectiva do aluno - Rodrigues, Eglen Sílvia Pípi (2004)
This work aimed to investigate what vision children in the first grades in urban suburban public school have about the school situation . The goals of this work were: to discover how children describe, analize and qualify the types of learning they acquire at school, to realize what types of relationship they develop with the institution; to verify if there is any relation between content which is taught at school and their lives. The literature chosen for the data analysis intended to discuss some important concepts about this issue, such as: the democratization of public learning, the individuals in the school universe, their relation to knowledge, the dialogistical relation in the classroom, among other. The research was conducted by means of semi-structed interviews with four boys and two girls that attended the same school, but had diversed school performance. The interviews occurred in two different moments: at first, when all of them attended the fourth grade in Brazilian elementary school (2001) and, later, when four of them attended the fifth grade and two remained in the previous grade, after having failed the exams (2002). Data have shown that the perception those boys and girls have about the function of school involves both the socialization that the institution promotes (social intimacy and insertion) and its role as a formative agent (in content and citizenship formal/instrumental). As for their effective learning, data have shown that those children have learned the socialization content, but not all of them have had access to the formal/instrumental content: after having failed the exams for several times, once more the two oldest boys finished the fourth grade in Brazilian elementary school without being able to read and write, and they resented that. Listening to boys and girls and with them stablishing an open dialog about school and learning has proved to be an absolute need in the construction of a more democratic and democratizing school.